The Correlation Between Students’ Motivation And Learning Styles Towards Students’ English Achievement In The State Polytechnic Of Lampung - Yusep Windu Ari Wibowo (Jurnal Ilmiah ESAI, 2013)
The objective of this research is to find out whether there are any correlations between students’ motivation and learning styles toward their English achievement. motivation and learning styles have significant correlation toward their English achievement. Continuous learning styles of students with their motivation is a decisive performance improvement study English so that students will be more interested to deepen their knowledge. The material in this study is a questionnaire of learning styles, and motivation to know the students’ learning styles and motivation. In addition, as the material to determine the English proficiency of students, this study uses 200 multiple choice questions of TOEIC (Test of English for International Communication). The research method uses a correlation which is one type of research designed to determine the degree of correlation between the dependent variable and the independent variables, both individually using simple linear regression and simultaneous multiple linear regression. Instruments of learning motivation and learning styles of students using a questionnaire with Likert scale, while for the English proficiency test results obtained from the result of test.   The study was planned for 6 months April to September 2012 at the State Polytechnic of Lampung. 6 months used for the preparation, determine the sample, giving questionnaires, analyzing data, and seminars. The result of research and data analysis shows that there are closed positive correlation and significant between students’ motivation and learning styles toward their English achievement Key words : motivation, learning styles, achievement